Reaksi Pasar Modal Sebelum dan Sesudah Pengumuman Resesi Ekonomi di Indonesia pada Perusahaan Tambang yang Listing di BEI - Shafira Oktaviani, Raeta; Gennody Pronosokodewo, Baniady; Vitta Adhivinna, Vidya (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
This study aims to determine the difference in capital market reactions before and after announcement of economic recession in Indonesian at mining companies listed on IDX. The population in study all mining companies listed on Indonesian Stock Exchange (IDX) and reporting financial report in 2018-2021. The sample in study were 20 mining companies listed on Indonesian Stock Exchange (IDX). The sampling technique use was non-probability sampling technique by giving certain characteristics or called purposive sampling. The result of study show that 1) there is differences in abnormal return before and after Announcement of Economic Recession in Indonesian at Mining Companies listed on the IDX. 2) there is no difference in trading volume activity before and after Announcement of Economic Recession in Indonesian at Mining Companies listed on IDX.